MiR‐149 controls non‐alcoholic fatty liver by targeting FGF‐21. Issue 8 (6th April 2016) - Xiao, Junjie; Lv, Dongchao; Zhao, Yingying; Chen, Xiaoyu; Song, Meiyi; Liu, Jingqi; Bei, Yihua; Wang, Fei; Yang, Wenzhuo; Yang, Changqing
Abstract: Non‐alcoholic fatty liver disease (NAFLD), a lipid metabolism disorder characterized by the accumulation of intrahepatic fat, has emerged as a global public health problem. However, its underlying molecular mechanism remains unclear. We previously have found that miR‐149 was elevated in NAFLD induced by high‐fat diet mice model, whereas decreased by a 16‐week running programme. Here, we reported that miR‐149 was increased in HepG2 cells treated with long‐chain fatty acid (FFA). In addition, miR‐149 was able to promote lipogenesis in HepG2 cells in the absence of FFA treatment. Moreover, inhibition of miR‐149 was capable of inhibiting lipogenesis in HepG2 cells in the presence of FFA treatment. Meanwhile, fibroblast growth factor‐21 (FGF‐21) was identified as a target gene of miR‐149, which was demonstrated by the fact that miR‐149 could negatively regulate the protein expression level of FGF‐21, and FGF‐21 was also responsible for the effect of miR‐149 inhibitor in decreasing lipogenesis in HepG2 cells in the presence of FFA treatment. These data implicate that miR‐149 might be a novel therapeutic target for NAFLD.